Implementation of Problem Based Learning Model to Improve Student Learning Outcomes on Energy Change Material at MI Nahdlatul Ulama Ngingas - Indrawati, Uty Sekar; Tristyani, Vivin; Hasanah, Uswatun; Andriani, Vivi (Jurnal Profesi Guru Indonesia, 2024)
This study aims to determine the application of the Problem Based Learning (PBL) model in improving student learning outcomes on energy change materials in class IVB MI Nahdlatul Ulama Ngingas, Waru, Sidoarjo. This study uses a Classroom Action Research (PTK) approach which consists of two cycles, with each cycle including planning, implementation, observation, and reflection. The data sources in this study include student pretest and posttest results, observations of learning activities, and interviews with students and teachers. The results of the study show that the application of the PBL model can significantly improve student learning outcomes. Before the implementation of PBL, only 50% of students achieved the Minimum Completeness Criteria (KKM), with an average class score of 65. After the implementation of the PBL model, as many as 85% of students achieved grades above the KKM, with the average grade increase to 78. In addition, students also show improvements in critical thinking skills and the ability to collaborate. Based on these findings, it can be concluded that the PBL model is effective in improving student learning outcomes on energy change materials, as well as helping students develop problem-solving and collaboration skills.